Cultivation of the causative agent of human neoehrlichiosis from clinical isolates identifies vascular endothelium as a target of infection - Linda Wass; Anna Grankvist; Lesley Bell-Sakyi; Malin Bergström; Erik Ulfhammer; Christine Lingblom; Christine Wennerås (Emerging Microbes and Infections)
Candidatus (Ca.) Neoehrlichia mikurensis is the cause of neoehrlichiosis, an emerging tick-borne infectious disease characterized by fever and vascular events. The bacterium belongs to the Anaplasmataceae, a family of obligate intracellular pathogens, but has not previously been cultivated, and it is uncertain which cell types it infects. The goals of this study were to cultivate Ca. N. mikurensis in cell lines and to identify possible target cells for human infection. Blood components derived from infected patients were inoculated into cell lines of both tick and human origin. Bacterial growth in the cell cultures was monitored by real-time PCR and imaging flow cytometry. Ca. N. mikurensis was successfully propagated from the blood of immunocompromised neoehrlichiosis patients in two Ixodes spp. tick cell lines following incubation periods of 7–20 weeks. Human primary endothelial cells derived from skin microvasculature as well as pulmonary artery were also susceptible to infection with tick cell-derived bacteria. Finally, Ca. N. mikurensis was visualized within circulating endothelial cells of two neoehrlichiosis patients. To conclude, we report the first successful isolation and propagation of Ca. N. mikurensis from clinical isolates and identify human vascular endothelial cells as a target of infection.